PENGARUH KOMPETENSI KERJA, MOTIVASI DAN DUKUNGAN ORGANISASI PERUSAHAAN TERHADAP KINERJA KARYAWAN PADA PT INDMIRA YOGYAKARTA - Raydhika Ardhi Siwi; Karnowahadi Karnowahadi; Inayah Inayah (Politeknik Negeri Semarang, 2018)
This research is conducted at PT Indmira Yogyakarta a private company engaged in agrocomplex since 1985 and established by Ir. Sumarno. To continue to maintain and improve the quality of existing products, the company consider the importance of effort to develop the performance of its employees. For the purpose of this study, aspects that can affect employee performance are analyzed those affects are work competence, motivation and organizational support. The methods of data collection used in this study are interviews, literature studies and questionnaires. Questionnaires in this study use Likert measurement scale by giving a score of 1-5 on the answers, and sampling uses Probability Sampling technique for 65 samples. The method of analysis uses are validity test, reliability test, multiple linear regression, classic assumption, coefficient determination, F test and t test. Result of this research obtains value of adjusted R square equal to 0,395. This means that work competence, motivation, and organizational support influence 39,5% employee performance. The equation resulted from multiple linear regression is Y = 6,256 + 0,389X1 + 0,059X2 + 0,324X3. The meaning of the equation are work competence variable (X1) has a positive and significant effect on employee performance (Y) with coefficient value of 0.389. Variable of motivation (X2) have positive but not significant effect on employee performance (Y) with coefficient value equal to 0,059. Variable organizational support (X3) has positive and significant effect to employee performance (Y) with coefficient value equal to 0,324. So Of the three variables, work competence variable (X1) has the greatest effect on employee performance (Y) of 0.389. It is recommended that if the company wants to improve employee performance significantly, it can be by considering the competence of work owned by its employees. because From the results of multiple linear analysis, work competence has the greatest influence compared to motivation and organizational support.